Assay of Ascorbic Acid in Plants Tissues, I: 1H and 13C NMR Study of the Complex between Cu(I) and 2,2'.Biquinohne. - GAVINO PINNA, GIAN; LUISA GANADU, MARIA; CRISPONI, GUIDO; NlRRCHI, VALERIA (Asian Journal of Chemistry, 2010)
The Shieh's method, originally devised for the analysis of ascorbic acid (AsA) in pharmaceutical preparations and based on the reaction of this acid with Cu(I) and 2,2´-biquinoline, was adapted to determine AsA in biological samples and particularly in plant tissues. The proposed assay is compared with some current methods for AsA determination. Moreover the system Cu(I)-biquinoline is studied by 1H and 13C NMR spectroscopy, and a coordination model for the complex is proposed.